2019
DOI: 10.3168/jds.2018-15434
|View full text |Cite
|
Sign up to set email alerts
|

Modeling missing pedigree in single-step genomic BLUP

Abstract: The objective was to compare methods of modeling missing pedigree in single-step genomic BLUP (ssGB-LUP). Options for modeling missing pedigree included ignoring the missing pedigree, unknown parent groups (UPG) based on A (the numerator relationship matrix) or H (the unified pedigree and genomic relationship matrix), and metafounders. The assumptions for the distribution of estimated breeding values changed with the different models. We simulated data with heritabilities of 0.3 and 0.1 for dairy cattle popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 24 publications
6
36
0
2
Order By: Relevance
“…However, SSGBLUP-EUPG model was biased ( ), which indicates inflation of EBV. This agrees with [ 18 ] who found that SSGBLUP-EUPG was biased. In Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…However, SSGBLUP-EUPG model was biased ( ), which indicates inflation of EBV. This agrees with [ 18 ] who found that SSGBLUP-EUPG was biased. In Fig.…”
Section: Resultssupporting
confidence: 93%
“…Estimates of bias, dispersion and accuracy were obtained with evaluation models that used only pedigree or a combination of pedigree and genomic relationship matrices with different strategies to model missing pedigree and using the LR method. The properties of such types of models have recently been extensively investigated [ 18 , 30 , 36 40 ]. The current study adds further evidence that the metafounder approach should be the preferred one for genomic evaluation across species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In those years, young sons of strongly selected top proven sires, as well as old elite bulls born before 2008, were genotyped. Another reason was an improper definition of unknown parent groups (UPG) assigned for missing parents (Bradford et al, 2019;Tsuruta et al, 2019). When Bias in genomic predictions by mating practices for linear type traits in a large-scale genomic evaluation S. Tsuruta, 1 * T. J. Lawlor, 2 D. A. L. Lourenco, 1 and I. Misztal 1 animals with no phenotypes or few animals are assigned to UPG, the UPG cannot be accurately estimated.…”
Section: Introductionmentioning
confidence: 99%